2018
DOI: 10.1038/s41419-018-0708-5
|View full text |Cite
|
Sign up to set email alerts
|

Succinate induces aberrant mitochondrial fission in cardiomyocytes through GPR91 signaling

Abstract: Altered mitochondrial metabolism acts as an initial cause for cardiovascular diseases and metabolic intermediate succinate emerges as a mediator of mitochondrial dysfunction. This work aims to investigate whether or not extracellular succinate accumulation and its targeted G protein-coupled receptor-91 (GPR91) activation induce cardiac injury through mitochondrial impairment. The results showed that extracellular succinate promoted the translocation of dynamin-related protein 1 (Drp1) to mitochondria via prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 43 publications
5
28
0
Order By: Relevance
“…The expression of GPR91 was validated in H9C2 cells by immunofluorescence staining, in accordance to similar observations by other authors [ 36 ], suggesting that this receptor may be strongly implicated in the protective effects of cis -ES and SUC. However, to ensure and validate the crucial role of the GPR91 receptor in the observed protective effects, a receptor knockout should be performed, as already reported [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The expression of GPR91 was validated in H9C2 cells by immunofluorescence staining, in accordance to similar observations by other authors [ 36 ], suggesting that this receptor may be strongly implicated in the protective effects of cis -ES and SUC. However, to ensure and validate the crucial role of the GPR91 receptor in the observed protective effects, a receptor knockout should be performed, as already reported [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, some authors reported that GPR91 induces cardiac hypertrophy [ 15 , 35 ], while others observed that a prolonged incubation of cardiomyocytes with high concentrations of succinate (10 mM) promoted apoptosis [ 16 ]. Similar observations were made in the context of an ischemic injury, where the release of succinate and the triggering of the GPR91-associated signaling pathway were responsible for mitochondrial dysfunction and apoptosis in cardiomyocytes [ 36 ]. In the present study, although both agonists significantly reduced the DOX-induced overactivity of caspase 3, SUC alone induced an increased activity of caspase 3, while no such effect was found for cis -ES alone.…”
Section: Discussionsupporting
confidence: 69%
“…The modest reduction in RET we observed was also associated with improved cristae ultrastructure. Accordingly, it might be hypothesized that succinate accumulation induces RET, which has been associated with mitochondrial fragmentation 89 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, byproducts of glycolysis and the Kreb cycle, such as lactate and succinate, respectively, have been shown to alter the activities of multiple immune cell types. Succinate, in addition to its role as a Krebs cycle intermediate, acts as a chemical messenger to induce inflammatory responses, 69 and lactate promotes proinflammatory phenotypes in T cells 70 and promotes an anti-inflammatory phenotype in monocytes. 71 Exercise is well known to promote succinate and lactate accumulation; 72 thus, increases in these metabolites may play a role in regulating immunity.…”
Section: Immunometabolism: Exercise-induced Immune Cell Energy Demandmentioning
confidence: 99%